Responding to patient safety incidents: the "seven pillars". Issue 6 (1st March 2010) - McDonald, T B; Helmchen, L A; Smith, K M; Centomani, N; Gunderson, A; Mayer, D; Chamberlin, W H
Abstract : Background: Although acknowledged to be an ethical imperative for providers, disclosure following patient safety incidents remains the exception. The appropriate response to a patient safety incident and the disclosure of medical errors are neither easy nor obvious. An inadequate response to patient harm or an inappropriate disclosure may frustrate practitioners, dent their professional reputation, and alienate patients. Methods: The authors have presented a descriptive study on the comprehensive process for responding to patient safety incidents, including the disclosure of medical errors adopted at a large, urban tertiary care centre in the United States. Results: In the first two years post-implementation, the "seven pillars" process has led to more than 2, 000 incident reports annually, prompted more than 100 investigations with root cause analysis, translated into close to 200 system improvements and served as the foundation of almost 106 disclosure conversations and 20 full disclosures of inappropriate or unreasonable care causing harm to patients. Conclusions: Adopting a policy of transparency represents a major shift in organisational focus and may take several years to implement. In our experience, the ability to rapidly learn from, respond to, and modify practices based on investigation to improve the safety and quality of patient care is grounded in transparency.